FORMATION AND CHARACTERIZATION OF MULTICOMPONENT CRYSTAL OF TRIMETHOPRIM AND MANDELIC ACID BY SOLVENT DROP GRINDING METHOD - FITRIANI, LILI; FADINA, HUMAIRA; USMAN, HENDRIZAL; ZAINI, ERIZAL (International Journal of Applied Pharmaceutics, 2023)
Objective: To increase the solubility of trimethoprim by forming multicomponent crystals using mandelic acid as a coformer. Methods: Multicomponent crystals of trimethoprim and mandelic acid were prepared at a ratio of 1:1 mol by the Solvent Drop Grinding (SDG) method. Solid state characterization was carried out using Differential Scanning Calorimetry (DSC), Powder X-ray Diffraction (PXRD), Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscope (SEM), and polarized microscope. The solubility test of trimethoprim was carried out in CO2-free distilled water using a sonicator for 5 min and then determined by High-Performance Liquid Chromatography (HPLC) using acetonitrile and phosphoric acid in a 10:90 ratio as the mobile phase and octadecylsilane (C18) as the stationary phase. Results: The results showed a decrease in the melting point and enthalpy of fusion on the DSC thermogram, a new peak in the X-ray diffraction pattern, and a slight shift of wave number in the FTIR spectroscopy. Those characterizations indicated that the multicomponent crystal formed a salt type. SEM analysis showed morphological changes and formation of new crystal habits. The polarization microscopy analysis showed birefringent with various colors in all samples. The solubility of multicomponent crystal is 2.73-times higher compared to intact trimethoprim. Conclusion: The formation of cocrystals of trimethoprim and mandelic acid by SDG method increased the solubility of trimethoprim.